Overview of Life Cycle Assessment of Current Emerging Technologies - Cicilia Sriliasta; Vivi Meilinda (Pandawan Sejahtera Indonesia, 2023)
For its potential to facilitate the development of cutting-edgetechnologies with enhanced environmental performances,projected useat basic levels of life cycle analysis (LCA)technological readiness levels (TRL) has attracted enormousinterest in recent literature. But the normal LCA standardsfind it very difficult to evaluate developing technologies,necessitating methodological advancements in the presentLCA framework due to inadequate data, questionablefunctioning, scale-up problems, and uncertainties. We reviewpublished literature in this paper to identify majormethodological challenges and key research efforts to addressthese issues, with a focus on recent developments in five keyareas: cross-study comparability, data availability and quality,scale-up issues, uncertainty and uncertainty communication,and assessment time. Additionally, we provide a number ofsuggestions for further study to assist in the assessment of newtechnologies at low technical readiness level: (1) the creation of auniform framework and reporting procedures for life cycleassessments (LCAs) of developing technologies; (2) theincorporation of additional tools with LCA; and (3) the creation of adata repository for cutting-edge materials, procedures, andtechnologies. Decision-making techniques, such as multicriteriadecision analysis, risk analysis, and techno-economic analysis.